Measuring Women's Covert Use of Modern Contraception in Cross‐Sectional Surveys. Issue 2 (30th May 2018) - Choiriyyah, Ifta; Becker, Stan
Abstract: A proportion of women in couples use contraception without their partners' knowledge. There are two principal ways to measure this covert use in cross‐sectional surveys like the Demographic and Health Surveys (DHS). First is a direct question, "Does your husband/partner know that you are using a method of family planning?" Second is an indirect method: the reports of both partners to the question on contraceptive use are matched, and if the woman reports a modern contraceptive method and the male partner reports nonuse, her use is considered covert. For 21 DHS surveys for which both estimates could be made, there are large discrepancies between the two. We found that a proxy variable—responses to the question, "Would you say that using contraception is mainly your decision, mainly your husband's/partner's decision, or did you both decide together?"—has high sensitivity and specificity for classifying those in the open category for both methods and those in the covert category for both methods. Recommendations are that the direct question be reinstated in the DHS and that the indirect method not be used by itself but in conjunction with the decision‐making variable.